Solid-state conformational isomerism lacking a gas-phase energy barrier: its structural, spectroscopic, and theoretical identification in an organochromium(III) complex - Hansen, Helge-Boj; Krzystek, J.; Telser, Joshua; Swain, Abinash; Rajaraman, Gopalan; Wadepohl, Hubert; Enders, Markus (Organometallics, 2022)
We present a combined X-ray diffraction (XRD), high-frequency and -field electron paramagnetic resonance (HFEPR), and theoretical study of an organochromium(III) complex with relevance to polymerization catalysis that crystallizes in a disordered structure with two conformational isomers in a ratio of 0.89:0.11. The structure is exceptional, as the disorder is restricted to the CrCl2 moiety, whereas the organic ligand is not disordered within the precision of the structure determination. Although the geometry is only slightly varied, these Cr(III) (3d3, S = 3/2) isomers give substantially different EPR spectra so that both species can be analyzed in terms of distinct zero-field splitting (zfs) parameters. Using the solid-state molecular structure of each isomer, calculated spin Hamiltonian parameters using high-level ab initio methods are in good accordance with the experimental results. However, no energy barrier could be identified by calculation of the gas-phase molecular structure, leading to the conclusion that the occurrence of the two isomers is due to intermolecular interactions in the solid state. These results highlight the subtle structural differences that can exist in organometallic complexes. Such structural conformations might well be accessible in solutions of precatalysts and active polymerization catalysts affecting their reactivity.
Published online 9 June 2022
Gesehen am 29.11.2022